De(s)colonizing economics: evidence of a transmodern transdevelopment in Mexico - Téllez-Cabrera, Marco Ricardo; García-García, Gabriela (Iberoamerican Journal of Development Studies, 2025)
The planetary crises, the misdevelopment of humanity, and the idea of continuous economic growth without limits have led to a series of criticisms of the modern metanarrative of development. The proposal of transdevelopment, as a transmodern paradigm of well-being in which otherness is present, allows for framing other ways of doing economy, different from the convention and, in this sense, de(s)colonizes economics. This research conceptualizes categories associated with transdevelopment and economics and presents five cases of transdevelopment experiences/proposals in Mexico using qualitative methodology in the form of documentary and case analysis. Perspectives of life compatible with relational ontologies, attributable to the indigenous tradition, were found, which account for rationalities different from that of homo economicus. These rationalities, not centered on accumulation, allow for generating alternatives to the conventional market and visualizing it as complementary.